The consumer's rescission right in terms of the National Credit Act 34 of 2005 : a comparison with similar rights in terms of other consumer protection legislation - Renke, Stefan (University of Pretoria, 2025)
Mini Dissertation (LLM (Consumer Protection))--University of Pretoria, 2024.